Thermal stability effect of H4[PVMo11O40]/SiO2 - Leni Sinaga; Aldes Lesbani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2017)
Synthesis and characterization of supported polyoxometalate H4[PVMo11O40].nH2O with SiO2 through sol-gel method have been done. The compound H4[PVMo11O40]/SiO2 was characterized through FT-IR spectrophotometer, XRD, and SEM-EDX. The results showed that FT-IR spectrum of H4[PVMo11O40]/SiO2 has the primary vibration on wavenumber at 1064.7 cm-1 (P-O); 964.4 cm-1 (Mo=O); 864.1 cm-1 (Mo-Oe-Mo); 779.2 cm-1 (Mo-Oc-Mo); 462.9 cm-1 (Si-O); and 1087.9 cm-1 (Si-O-Si). The XRD diffraction pattern showed that H4[PVMo11O40].nH2O has the highest crystallinity. However, after it’s supported with SiO2, the properties of crystallinity has decreased due to the excess water during the support process. The result of SEM-EDX showed that H4[PVMo11O40]/SiO2 material has homogeneous distribution with particle size distribution of 1330 nm (1,33 μm). The acidity test by qualitative and quantitative methods show that H4[PVMo11O40]/SiO2 more acidic than H4[PVMo11O40].H2O. The effect temperature on the crystallinity showed that increasing calcination temperature made the crystallinity properties of H4[PVMo11O40]/SiO2 increased. Keywords : polyoxometalate, H4[PVMo11O40].nH2O, SiO2.